2005
DOI: 10.1373/clinchem.2005.054460
|View full text |Cite
|
Sign up to set email alerts
|

Early Enhanced Expression of Interferon-Inducible Protein-10 (CXCL-10) and Other Chemokines Predicts Adverse Outcome in Severe Acute Respiratory Syndrome

Abstract: Increased plasma IP-10 during the first week of SARS symptoms is an independent predictor of outcome. Chemokine activation may be an early event in SARS, and an exaggerated host response may produce complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
191
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(202 citation statements)
references
References 33 publications
(45 reference statements)
8
191
0
3
Order By: Relevance
“…However, culturing and infecting the type II cell at an air-liquid interface (A/L) allowed for significant infection and characterization of their innate immune response. The robust innate immune response of these cells to SARS-CoV infection consisted of marked elevations in mRNA concentrations of interferon-b, interferon-l, CXCL10, CXCL11, and IL-6, and these results mirror findings reported in the lungs and sera of patients with SARS (22,23,25).…”
Section: Clinical Relevancesupporting
confidence: 74%
See 2 more Smart Citations
“…However, culturing and infecting the type II cell at an air-liquid interface (A/L) allowed for significant infection and characterization of their innate immune response. The robust innate immune response of these cells to SARS-CoV infection consisted of marked elevations in mRNA concentrations of interferon-b, interferon-l, CXCL10, CXCL11, and IL-6, and these results mirror findings reported in the lungs and sera of patients with SARS (22,23,25).…”
Section: Clinical Relevancesupporting
confidence: 74%
“…Concentrations of multiple proinflammatory cytokines and chemokines have been reported to be increased in the lungs and sera of patients with SARS (22,23,25,26). Because alveolar type II cells at the A/L were readily infected by SARS-CoV, we were able to measure changes in expression of selected genes of the innate immune system in these cells in response to SARS-CoV infection ( Figure 5).…”
Section: Alveolar Type II Cell Cultures At the A/l Display A Vigorousmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently accumulated evidence has demonstrated an elevated serum IP-10 level in various diseases, including inflammatory disease, and has shown its utility as a clinically useful biomarker. [13][14][15] For instance, Tang et al 16 demonstrated that IP-10 is an independent predictor of outcome for severe acute respiratory syndrome patients. Another group has demonstrated elevated IP-10 levels in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…In case of coronavirus infection, either MERS-CoV or SARSCoV, it was observed that virus infection induces an excessive activation of the immune system which leads to the synthesis of several pro-inflammatory cytokines like interleukin-1beta (IL-1B), IL-6, IL-8, CXC-chemokine ligand 10 (CXCL10), CC-chemokine ligand 2 (CCL2), and interferon-γ (IFN-γ) [9][10][11][12]. This proinflammatory response will ultimately induce pulmonary circulation capillary leakage which will lead to non-cardiogenic pulmonary edema, hypoxemia, type II pneumocyte hyperplasia, and neutrophil infiltration.…”
mentioning
confidence: 99%